Breath Failure in Obesity - Wirya Sastra Amran; Putri Suci; Nina Aspiah; Menaldi Rasmin; Prasenohadi Prasenohadi; Agus Dwi Susanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Based on calculations of over one million people in the world weighing excessively or known as obesity with body mass index (IMT) 25 kg / m2 or more. Obesity is the cause of morbidity, as is the case in the population of the United States an estimated 400,000 deaths caused due to obesity. Obesity especially abdominal obesity is a significant risk factor for cardiovascular diseases, type 2 diabetes, rheumatoid arthritis and cancer. The relationship between obesity and chronic respiratory illness began to increase and began to be recognized. The World Health Organization (WHO) predicts about 10% of the global population will be obese by 2015. (J Respir Indo 2018; 38(2): 123-33)